THERE IS NO INDIGENOUS WORD TO SAY TOURISM. LARGE-SCALE TOURISM AND ITS IMPACT ON GUARANÍ POPULATIONS. - Enriz, Noelia (2020)
This paper addresses the creation of protected natural areas in territories of ancestral indigenous occupation, especially when protected areas develop as poles of international tourism. The study discusses the specific case of large-scale tourism in the Iguazu area in northern Argentina. The Iguazu Falls are located at Iguazu, which is the most relevant tourist point in the country. This inquiry is part of long-term projects in the area within the framework of historical-ethnographic research methodologies. On an empirical standing, we use documentary sources, ethnographic records, and conversation fragments. On the theoretical level, the aim of this paper is to contribute to the field with reflections on extractive industries, conflicts between environment, conservation, and socio-environmental impact from an ethnographic perspective focused on indigenous populations.